Executarea silită și interesul superior al copilului – puncte de joncțiune [Articol] - Novicov, Oxana (CEP USM, 2022)
Forced execution can interfere with the right and interest of the child directly - when documents are executed regarding the custody of the child or the right to meet with him, when payments are collected for his maintenance; but also indirectly - when the execution is carried out on the assets of the debtor's family. The article envisages problems and lacks of regulation regarding executions that directly affect the rights of minors and offers suggestions for solutions for them.
Keywords: alimony; minor; executarea silită